Rola matki w wychowaniu i kształceniu dzieci w świetle artykułów z krakowskich czasopism kobiecych "Niewiasty" i "Kaliny" - Stawiak-Ososińska, Małgorzata (Karkonoska Państwowa Szkoła Wyższa, 2011)
In the second half of the 19 century appeared periodicals addressed to women, in which discussion on the place and role of the woman in society and family was raised. Among the most readable and representing relatively high level were found periodicals 'Niewiasta' and 'Kalina'. Most of the articles published in those periodicals were devoted to mother, as the first educator and teacher of her children. From the analysis of the works emerges a picture of a caring mother, providing safety and development of her children, bringing up children in the spirit of patriotism and love of God, as well as aspiring to educate her offspring to be citizens and members of the polish society. Principally attention was focused on the role of mother inupbringing daughters. It was clearly pointed out, that it was the mother whom the future of her children depended on. The aim of the maternal influence was to form a person possessing numerous virtues and abilities essential to become a good wife, mother and housewife. The mother was moreover supposed to be an inseparable companion of her children, their support in troubles as well as mentor introducing young generation into the vortex of national, social and family life.
Keywords: women; Poland 19th century; mother; upbringing; women's magazines